2008
DOI: 10.4049/jimmunol.181.12.8425
|View full text |Cite
|
Sign up to set email alerts
|

Induction of HIV Transcription by Nef Involves Lck Activation and Protein Kinase Cθ Raft Recruitment Leading to Activation of ERK1/2 but Not NFκB

Abstract: The Nef protein of HIV-1 is a key promoter of disease progression, owing to its dramatic yet ill-defined impact on viral replication. Previously, we have shown that Nef enhances embryonic ectodermal development Tat-mediated transcription in a manner depending on Lck and the cytoplasmic sequestration of the transcriptional repressor embryonic ectodermal development. In this study, we report that Lck is activated by Nef and targets protein kinase C downstream, leading to the translocation of the kinase into memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…This suggests that although GP120 signals primarily through CXCR4, CD4 or other molecules may also be needed [28]. The CD4-associated kinase Lck has recently ( 70,71 ) GP120 GP120 been linked to P38 activation [30]. In the past few years, it has been shown that P38a can also be activated through an ''alternative pathway'' in T cells [30].…”
Section: Hiv Infection and P38 Signalingmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests that although GP120 signals primarily through CXCR4, CD4 or other molecules may also be needed [28]. The CD4-associated kinase Lck has recently ( 70,71 ) GP120 GP120 been linked to P38 activation [30]. In the past few years, it has been shown that P38a can also be activated through an ''alternative pathway'' in T cells [30].…”
Section: Hiv Infection and P38 Signalingmentioning
confidence: 96%
“…Witte et al [70] found that HIV Nef can induce ERK1/2 signaling through Lck and PKCh recruitment to lipid rafts. Schrager et al [71] also showed that HIV Nef increased ERK activity in primary CD4 T cells.…”
Section: Hiv Infection and Erk Signalingmentioning
confidence: 98%
“…Note that hnRNP-K plays essential roles in transcriptional processes and molecular interactions (227). Overall, Nef exerts an impact on Tat-mediated transcription either by direct interaction or by signaling pathways mediated via cellular cofactors (223)(224)(225)(226). The exact protein domains that mediate the Tat-Nef interaction remain unclear.…”
Section: Tat-nef Interactionmentioning
confidence: 99%
“…First, Nef induces many host factors (e.g., CDK9, Tat-SF1, and IRF2) to promote Tat-mediated transcriptional activity (224). Second, Nef-mediated signaling can enhance Tat-mediated transcriptional activity via an extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase (MAPK)-dependent pathway (225). Third, Nef promotes Tat-mediated transcription via the heterogeneous nuclear ribonucleoprotein K (hnRNP-K)-nucleated signaling complex (226).…”
Section: Tat-nef Interactionmentioning
confidence: 99%
“…Though ERK and p38 MAPK signaling molecules can modulate T-cell function [14], these molecules have different effects on T-cell development, cell cycle progression, and apoptosis [23,24,25]. Also, it is significant that the MAPK signaling pathway is known to interact with HIV-1 viral proteins [26]. As shown in figure 2a, cotreatment of SAHA and TPA could induce HIV-1 reactivation via not the p38 MAPK pathway but the ERK pathway in HIV-1 latently infected cells (fig.…”
Section: Tablementioning
confidence: 99%